Omics technologies for an in-depth investigation of biodeterioration of cultural heritage. (October 2019) - Marvasi, Massimiliano; Cavalieri, Duccio; Mastromei, Giorgio; Casaccia, Antonella; Perito, Brunella
Abstract: Deterioration and degradation of works of art is of great concern to preserve humankind heritage. Among categories of degradation, biodeterioration is one of the main destructive type, considering the dynamic fluctuations that microorganisms exert on the substrate. In order to understand and cope with biological damage, the use of cutting-edge molecular techniques in combined multidisciplinary approaches is nowadays in its pioneering age. We provide a review on recent applications of omics technologies (genomics, transcriptomics, proteomics, metabolomics) to advance our understanding of microbial biodeterioration of cultural heritage materials such as stone, cellulose-based substrates, parchment. The interesting picture arising from this exercise is a fingerprint of biodegradation and its biological causes, identifying metabolites and microbial communities. At the end of the review we provide an extensive perspective section suggesting future approaches and concrete tools for conservators in diagnosis and treatment of biodeterioration. Highlights: Omics techniques improve the overall understanding of biodeterioration. Recent studies using omics approaches on different substrates are reviewed. Combined use of omics and cultivation techniques is emphasized. Perspectives and tools for biologists and conservators are suggested.